Fatal rupture of giant splenic artery pseudoaneurysm - Arun Prasad; Abhiranjan Prasad; Pradeep Kumar; Pranav Santhaliya (Elsevier, 2021)
Background: Pseudoaneurysm of splenic artery is an uncommon complication of blunt trauma to the abdomen. Most of such pseudoaneurysms are ≤3 cm in size. Rarely, its size may increase to ≥5 cm, to form a giant pseudoaneurysm, which has potential to rupture with fatal outcome. We report here a child who developed post-traumatic giant pseudoaneurysm of splenic artery measuring 8 cm × 7 cm in size. Giant pseudoaneurysm of splenic artery has not been reported in children so far. Besides reporting this case because of the size of the aneurysm in a child, we also want to emphasize the importance of early management of such case due to its potential to rupture, which could turn out to be a fatal complication. Case presentation: An eight-year-old boy presented to our hospital with complain of swelling over the abdomen after he sustained blunt trauma. Ultrasonography and CT demonstrated a giant splenic artery aneurysm. Patient was admitted for percutaneous coil embolization but before this procedure could be done, his pseudoaneurysm got ruptured spontaneously. This was followed by shock and cardiac arrest and he could not be revived despite our resuscitative efforts. Conclusion: A giant pseudoaneurysm should be treated as soon as possible to prevent life threatening complication due to its rupture.